Toxic elements in blood of red-necked nightjars (Caprimulgus ruficollis) inhabiting differently polluted environments - Espín Silvia; Sánchez-Virosta Pablo; Zamora-Marín José M.; León-Ortega Mario; Jiménez Pedro; Zumbado Manuel; Luzardo Octavio P.; Eeva Tapio; García-Fernández Antonio J. (Elsevier Ltd, 2022)
Toxic metals have been widely reported in avian tissues due to their well-known accumulation capacity and adverse effects. However, rare earth elements (REE) and other minor elements (ME) are becoming a new threat due to their use in modern technology. Presently, exposure data are limited and no studies have been reported in wildlife. The order Caprimulgiformes is among the most understudied groups of birds lacking blood ecotoxicological data. One major constraint is the small blood sample volume that can be collected to ensure animal welfare, which limits analyses. In order to shed light on these collective issues, we sampled 48 red-necked nightjars (Caprimulgus ruficollis) inhabiting three different scenarios of contaminant exposure (agricultural-urban area, n = 15; mining area, n = 17; and control area, n = 16) in southeastern Spain, and report for the first time concentrations of 50 elements (i.e. trace elements, ATSDR’s list toxic elements, REE and ME) using a recently developed technique able to analyze them by ICP-MS in very small volumes of blood (130 μL). Concentrations of As, Cd, Pb and Mn were significantly higher in individuals captured at the mining area compared to the other sites. Lead levels in the mine site were of particular concern since it was in the range of blood concentrations related to subclinical/clinical effects in other species, and in our study were associated with decreased hematocrit values (up to 44% hematocrit depression at blood concentrations >1000 ng/ml w.w.). Moreover, additive effects related to metal cocktail exposure in the mining area could be expected. Age and gender-related differences in blood concentrations were found for some elements. Even though most REE and ME concentrations were close to the LOQ, some of these emerging contaminants may trigger sublethal effects that, together with the ATSDR’s list toxic elements, need to be carefully evaluated in a future study.